2019
DOI: 10.1016/j.carbon.2019.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Systematic investigation of the catalyst composition effects on single-walled carbon nanotubes synthesis in floating-catalyst CVD

Abstract: Systematic investigation of the catalyst composition effects on single-walled carbon nanotubes synthesis in floating-catalyst CVD, Carbon (2019), doi:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 37 publications
1
52
0
1
Order By: Relevance
“…Interestingly, we found that the mean diameter of as-produced SWCNTs (~1 nm) is independent of catalyst composition under the similar NSD of catalyst particles. However, the yield, morphology and SWCNTs film conductivity can be effectively tuned by changing catalyst composition [11]. Furthermore, from the unambiguous electron diffraction technique, we observed that the bimetallic Co-Ni catalyst can produce comparatively narrower chirality and diameter distribution of SWCNTs.…”
Section: Introductionmentioning
confidence: 93%
See 4 more Smart Citations
“…Interestingly, we found that the mean diameter of as-produced SWCNTs (~1 nm) is independent of catalyst composition under the similar NSD of catalyst particles. However, the yield, morphology and SWCNTs film conductivity can be effectively tuned by changing catalyst composition [11]. Furthermore, from the unambiguous electron diffraction technique, we observed that the bimetallic Co-Ni catalyst can produce comparatively narrower chirality and diameter distribution of SWCNTs.…”
Section: Introductionmentioning
confidence: 93%
“…Fe (1.05 nm), e) Co (1.06 nm) and f) Co-Ni (0.99 nm) as catalyst particles. Image Copyright © 2019 Elsevier [11], used with permission.…”
Section: ) a Typical Sem Image Of Swcnts Bundles On Si/sio2 Substratementioning
confidence: 99%
See 3 more Smart Citations